Study on the Potential of Historical Mahogany Trees in Improving Urban Air Quality - Nuzir, Fritz Akhmad; Kurniawan, Andrew; Chandra, Sonia Dwi; Jamaludin; Munawaroh, Ai Siti (International Journal of Building, Urban, Interior and Landscape Technology, 2022)
Metro City is one of the cities in Lampung Province, Indonesia, which has experienced various infrastructure development which contributed to the decrease of the air quality. Urbanization also causes constant decrease in term of the number of green open spaces. Yet green open space plays an important role in maintaining urban air quality. Vegetation (i.e., tree) as the main component of green open space has the ability to absorb and store carbon emission. In Metro city, there is a major green open space that includes numerous large-sized Mahogany trees lining along A.H. Nasution Road. The purpose of this study was to estimate the level of air pollution from emissions of the passing-by motorized vehicles, calculate the capacity of carbon sequestration by the Mahogany trees, and determine the potential of the Mahogany trees in improving air quality. Authors collected primary data on the diameter of the tree trunks and the number of passing-by vehicles to estimate the carbon-storing capacity and carbon emission by utilizing allometric equation and emission load analysis. This study concluded that the Mahogany trees could play an important role on storing 74% of expected annual CO2 emission in Metro City. This could be linked to the achievement of the SDGs especially Target 11.6.